Do vermelho ao rosa: um estudo das estratégias de adaptação da personagem Sherlock para a TV - Oliveira, Cristina Imaculada Santana de (2021)
Sherlock Holmes is a century-old character who, due to his projection, came to obscure his creator, Arthur Conan Doyle, responsible not only for the conception of this solid detective character, but also for the construction of references that have influenced police narratives over time, a method of unique investigation based on logic and deduction. This character, drawn as a consulting detective, emerged in the novel A Study in Scarlet in 1887, and since then, numerous adaptations have been made, both in theater and in film on TV. More recently, in 2010, under the production of Mark Gatiss – the British writer, screenwriter and actor – and Steve Moffat – the Scottish screenwriter and producer, the Doylean creation got a re-writing the serial format with the title Sherlock. Of the four seasons produced, this dissertation investigated, in episode one (E1) of season one (T1) and in episode three (E3) of season four (T4), the new forms of consumption of the literary text in audiovisual language, and its insertion in a transnational telephilia or, as Silva (2014a) names it, in a series culture. As theoretical background for the discussions related to adaptation as literary rewriting within a cultural system, it was taken Lefevere (1992) and Even-Zohar (1990). In Esquenazi (2011), Balogh (2006), Reimão (1983), Jenkins (2009) and Jost (2012), it was found arguments to justify the importance of television series; and, in Hills (2015), Ndalianis (2004) and Mittell (2012), how the serial format for television is structured. The objective was to observe how the compositional elements of the Doylean character – updated by the Gatiss-Moffatiana rewriting – are presented in a contemporary context of television series, specifically regarding the construction of a repertoire that encourages the series culture. The bibliographical review showed that the range of academic researches on Conan Doyle is work still negligible, despite its vast amount of adaptations. This dissertation is based on the assumption that, even with changes in the original text, the character is recognized as a protagonist in the police novel genre, and that what could, at first, be a limiting factor in of directors’ creativity have showed, in the analysis of the television adaptation, that the strategies adopted by them expanded the readership and viewers of this literary genre, and turned the Sherlock series into an example of sophistication of the narrative form that encourages the viewer to dialogue with the Doylean text. In A Study in Pink – first episode of the series (T1E1) – the directors highlight the detective's characteristics, his logical method of investigation, the partnership with Watson – his inseparable comrade – within the current London context, highlighting the dilemmas of a post-modern metropolis. The four seasons were developed in a dynamic way and, in the last episode, The Final Problem (T4E3it is seen the evidential portrait of the psychological and affective deepening, not only of the detective, but also of his peers, in the formed acquaintanceship cares. This study has revealed that the serial reinforces elements of subtle psychological deepening in the source text that have been strengthened in the 21st century, full of conflicts, fragmentations, and emotional instabilities. The results have showed that the series, by exploring these resources and combining them with a technological apparatus and a powerful digital circulation, which reverberates in social media, offers a complex repertoire that feeds new possibilities for the creation of the oldest detective of the literary genre.